Bacterial Community Characteristics and Enzyme Activities in Bothriochloa ischaemum Litter Over Progressive Phytoremediation Years in a Copper Tailings Dam - Jia, Tong; Wang, Yuwen; Chai, Baofeng (Frontiers in Microbiology, 2020)
Litter decomposition is the key link between material circulation and energy flow in ecosystems, resulting from the activity of resident microbes and various enzymes. This study investigated enzyme activity in litter and associated microbial community characteristics to help clarify the internal mechanisms associated with litter decomposition, while also providing researchers a scientific basis for soil remediation in mining areas. Results confirmed that the nutrient content of Bothriochloa ischaemum litter significantly increased as phytoremediation years progressed, while enzyme activities in litter varied over different phytoremediation years. During the litter decomposition process, cellulase predominated in the early phytoremediation stage and catalase predominated in the intermediate phytoremediation stage. Obvious differences were found in bacterial community structure and litter diversity over progressive phytoremediation years. Predominant bacterial genera mainly included Massilia, Sphingomonas, Curtobacterium, Amnibacterium and Methylobacterium. Moreover, Methylorosula and Jatrophihabitans had relatively higher betweenness centrality, and played important roles in bacterial community positive interactions. Additionally, total nitrogen (TN) and total zinc in soil, sucrase and catalase activity in litter were the main environmental factors that affected the structural framework of bacteria in B. ischaemum litter. However, TN had the greatest overall effect on the structural framework of bacteria in litter. Results from this study can help our understanding of the role that litter plays in degraded ecosystems. Our results also provide a scientific basis for improving poor quality soil in areas affected by copper tailings while also amending ecological restoration efficiency.